Acceptability of Rapid Diagnostic Test-Based Management of Malaria among Caregivers of Under-Five Children in Rural Ghana - Baiden, Frank (Public Library of Science, 2012)
INTRODUCTION: WHO now recommends test-based management of malaria (TBMM) across all age-groups. This implies artemisinin-based combination treatment (ACT) should be restricted to rapid diagnostic test (RDT)-positive cases. This is a departure from what caregivers in rural communities have been used to for many years. METHODS: We conducted a survey among caregivers living close to 32 health centres in six districts in rural Ghana and used logistic regression to explore factors likely to influence caregiver acceptability of RDT based case management and concern about the denial of ACT on account of negative RDT results. Focus group discussions were conducted to explain the quantitative findings and to elicit further factors. RESULTS: A total of 3047 caregivers were interviewed. Nearly all (98%) reported a preference for TBMM over presumptive treatment. Caregivers who preferred TBMM were less likely to be concerned about the denial of ACT to their test-negative children (O.R. 0.57, 95%C.I. 0.33–0.98). Compared with caregivers who had never secured national health insurance cover, caregivers who had valid (adjusted O.R. 1.30, 95% CI 1.07–1.61) or expired (adjusted O.R. 1.38, 95% CI 1.12–1.73) insurance cover were more likely to be concerned about the denial of ACT to their RDT-negative children. Major factors that promote TBMM acceptability include the perception that a blood test at health centre level represents improvement in the quality of care, leads to improvement in treatment outcomes, and offers opportunity for better communication between health workers and caregivers. Acceptability is also enhanced by engaging caregivers in the procedures of the test. Apprehensions about negative health worker attitude could however undermine acceptance. CONCLUSION: Test (RDT)-based management of malaria in under-five children is likely to be acceptable to caregivers in rural Ghana. The quality of caregiver-health worker interaction needs to be improved if acceptability is to be sustained.